Traditional Agroforestry Systems and Food Supply under the Food Sovereignty Approach - Mariana Yazzur Hernández; Pedro Antonio Macario; Jorge Omar López (Ethnobiology Letters, 2017)
Intensive production systems have damaged many natural ecosystems and have altered their capacity to provide ecosystem services such as climate regulation, soil fertility, and vector-borne disease control. Therefore, these agroecosystems are unsustainable and poorly resilient. However, traditional agroforestry systems (TAS) contribute to the conservation of biodiversity and to the provision of inputs for the maintenance of local populations. The objective of this study was to evaluate the contribution of the TAS in the food supply under the food sovereignty (FSv) approach in three different ethnic groups. The study was conducted in three communities of different origin in the State of Campeche, one Maya Tseltal-Chol, the other Mestizo, and the third Yucatec Mayan. The theoretical-methodological framework of this research was based on agroecology. Ethnographic methods and participatory research activities were carried out to describe and analyze the factors that strengthen FSv using five indicators. Our results present a description and analysis of resource access, current production models, patterns of consumption and food security, commercialization and participation in decision-making of these communities. Traditional agroecological management practices are still preserved and native species are still being cultivated. Farmers obtain about 55% of their food from TAS. The consumption of food is influenced by the culture, the purchasing power linked to economic activities and government support. TAS have played a strategic role for the survival of families but to ensure their contribution to FSv, it is necessary to articulate the actions of the sectors that share the same objective and encourage the active participation of communities in agricultural policies.